2003
DOI: 10.1007/s00192-002-1022-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in familial dysautonomia

Abstract: The aim of this study was to determine the prevalence of urinary incontinence in women with familial dysautonomia (FD). A telephone survey was conducted on 68 known surviving female FD patients over 13 years of age registered with the Dysautonomia Centers in the USA and Israel. The mean age of the surveyed group was 27.1+/-9.8 years and 99% of the patients were nulliparous. The overall reported prevalence of urinary incontinence was 82% (n=56). Of the patients with incontinence, 59% (n=33) reported stress inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Renal perfusion improves at night when adopting the supine position, resulting in improved glomerular filtration and urine output . Nocturnal polyuria has been reported in other neurological disorders associated with cardiovascular dysautonomia, such as familial dysautonomia, where biopsies in individuals with renal impairment demonstrate ischemic‐type glomerulosclerosis and deficient vascular innervation . Studies in healthy elderly men with nocturnal polyuria have demonstrated alterations in the circadian pattern of blood pressure variations, increased daytime mean arterial blood pressure, nocturnal natriuresis, and reduced angiotensin II and arginine vasopressin levels, compared to controls .…”
Section: Discussionmentioning
confidence: 99%
“…Renal perfusion improves at night when adopting the supine position, resulting in improved glomerular filtration and urine output . Nocturnal polyuria has been reported in other neurological disorders associated with cardiovascular dysautonomia, such as familial dysautonomia, where biopsies in individuals with renal impairment demonstrate ischemic‐type glomerulosclerosis and deficient vascular innervation . Studies in healthy elderly men with nocturnal polyuria have demonstrated alterations in the circadian pattern of blood pressure variations, increased daytime mean arterial blood pressure, nocturnal natriuresis, and reduced angiotensin II and arginine vasopressin levels, compared to controls .…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] Further research might explore the choice of product and the personal struggles that may occur. [48][49][50] Further research might explore the choice of product and the personal struggles that may occur.…”
Section: ■ Discussionmentioning
confidence: 99%
“…66 Nighttime bladder control is usually achieved at a later age than in normal children. Treatment with desmopressin should be avoided due to the propensity for hyponatremia.…”
Section: Renal and Urologic Treatmentsmentioning
confidence: 99%